Pengujian Implementasi Sistem Pengelolaan Keuangan Masjid Berbasis Web Dan Android - Fachruddin Fachruddin; Muhammad Riza Pahlevi; Muhammad Ismail; Errissya Rasywir (LPPM Universitas Bina Sarana Informatika, 2020)
Manual financial management is one of the causes of data loss and report files. Meanwhile, financial reports are data that must be accounted for. As with our observations, the Darusalam Mosque (Pakuan Baru Village in Jambi City) quite often experiences these classic problems. With the use of Android-based application technology, it is hoped that the mosque's financial data will be more organized, neatly archived and transparent. The digital financial management or accounting system allows flexibility in accessing mosque financial reports. Therefore it is necessary to build a Mosque Financial Management System Based on the Android Platform. The Android-based financial management application will later be launched on Google Playstore, so that all parties who need this system can download this application for free. The application of applications with a whole series of good software engineering must be carried out in accordance with applicable business processes and do not change the flow of data and reports that have been running for years. The application of the Website-based application and the Android Platform that we did, was able to produce automatic and computerized mosque financial management and was considered very good in user testing